AIE Emission of SDS Capped Diphenylanthracene Nanoparticles for Selective Recognition and Estimation of Al3+ Ion in Aqueous Medium Based on Enhancement Effect and Analytical Application. Issue 1 (19th August 2020) - Suryawanshi, Sonali B.; Deshmukh, Gunvant R.; Bodake, Anita J.; Patil, Shivajirao R.
Abstract: The sodium dodecyl sulfate capped 9, 10 Diphenylanthracene nanoparticles is prepared by using reprecipitation method. The average particle size of NPs obtained from DLS examination is 67 nm. The aqueous suspension of NPs exhibits red shifted aggregation induces enhanced emission. The zeta potential value—42.9 mV indicates stability of NPs and generation of expected negative surface charge over the NPs to attract and adsorb cations from the solution on the surface. The cation recognition test based on fluorescence shows that the presence of Al 3+ ion significantly enhances the fluorescence of NPs. Furthermore, the proposed system is successfully applied for the detection of Al 3+ ion from environmental water samples and Digene table available in the market. The advantage of developed analytical method is lower value of LOD and even in presence of interfering ion Mg 2+ the Al 3+ is estimated with no need of their separation prior to analysis.